TOURIST ATTRACTIONS AND SERVICESCAPE AS EFFORTS TO INCREASE VISITING INTEREST ON HALAL TOURISM IN BIMA CITY - sri ernawati; ismunandar ismunandar (Tasharruf: Journal Economics and Business of Islam, 2021)
The natural and cultural wealth is a potential asset for tourism in Indonesia. The combination of tourist attractions and supporting facilities is a special advantage for tourists. The purpose of this study was to determine and partially analyze the influence of tourist attractions as an effort to increase visiting interest and servicescape as an effort to increase visiting interest and simultaneously tourist attractions and servicescapes in increasing tourist interest in visiting the concept of halal tourism in Bima City. The number of samples is 100 respondents with purposive sampling through a questionnaire with a Likert scale. Collecting data using questionnaires, observation, and literature study. Testing the data using SPSS (Statistical Package for the Social Sciences) version 20.0. Data analysis used multiple linear regression t-test, F test is carried out. The results show that tourist attractions have an effect as an effort to increase interest in visiting and servicescape has an effect as an effort to increase interest in visiting and simultaneously tourist attractions and servicescape have an effect together as an effort to increase interest in visiting halal tourism in Bima City